The anti-inflammatory effect of Sonchus oleraceus aqueous extract on lipopolysaccharide stimulated RAW 264.7 cells and mice - Qi Li; Dan-Dan Dong; Qiu-Ping Huang; Jing Li; Yong-Yong Du; Bin Li; Huan-Qing Li; Ting Huyan (Taylor & Francis Group, 2017)
Context: Sonchus oleraceus L. (Asteraceae) (SO) is a dietary and traditional medicinal plant in China. However, its underlying mechanism of action as an anti-inflammatory agent is not known. Objective: This study evaluates the anti-inflammatory activity of aqueous extract of SO. Materials and methods: The extract of SO was used to treat RAW 264.7 cells (in the working concentrations of 500, 250, 125, 62.5, 31.3 and 15.6 μg/mL) for 24 h. Pro-inflammatory cytokines and mediators produced in LPS-stimulated RAW 264.7 cells were assessed. Meanwhile, the expression level of TLR-4, COX-2, pSTATs and NF-κB was tested. Moreover, the anti-inflammatory activity of the extract in vivo was assessed using xylene-induced mouse ear oedema model and the anti-inflammatory compounds in the extracts were analyzed by HPLC-MS. Results: SO extract significantly inhibited the production of pro-inflammatory cytokines and mediators at gene and protein levels with the concentration of 31.3 μg/mL, and suppressed the expression of TLR-4, COX-2, NF-κB and pSTAT in RAW 264.7 cells. The anti-inflammatory activity of SO in vivo has significant anti-inflammatory effects with the concentration of 250 and 125 mg/kg, and less side effect on the weights of the mice at the concentration of 250 mg/kg. Moreover, HPLC-MS analysis revealed that the anti-inflammatory compounds in the extract were identified as villosol, ferulaic acid, β-sitosterol, ursolic acid and rutin. Discussion and conclusion: This study indicated that SO extract has anti-inflammatory effects in vitro and in vivo, which will be further developed as novel pharmacological strategies in order to defeat inflammatory diseases.